2017
DOI: 10.1136/bmjopen-2016-013019
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondiiexposure and Parkinson's disease: a case–control study

Abstract: ObjectivesTo determine the association between Toxoplasma gondii infection and Parkinson's disease and to investigate whether T. gondii seropositivity is associated with the general characteristics of patients with Parkinson's disease.DesignCase–control study.SettingCases and controls were enrolled in Durango City, Mexico.Participants65 patients with Parkinson's disease and 195 age- and gender-matched control subjects without Parkinson's disease.Primary and secondary outcome measuresSerum samples of participan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…The literature has also suggested other factors linked to PD. Among them, infection with Toxoplasma gondii might be implicated in the development of PD [ 288 ] (as well as schizophrenia [ 289 ] and AD [ 290 ]) or it may have had, at least, an influence on certain symptoms [ 291 ]. In a mouse study, the cortical neurodegeneration caused by chronic exposure to this neurotropic parasite led to increased CX3CL1 expression accompanied by microglia activation [ 292 ].…”
Section: The Role Of Changes In Cx3cl1-cx3cr1 and Cd200-cd200r Interamentioning
confidence: 99%
“…The literature has also suggested other factors linked to PD. Among them, infection with Toxoplasma gondii might be implicated in the development of PD [ 288 ] (as well as schizophrenia [ 289 ] and AD [ 290 ]) or it may have had, at least, an influence on certain symptoms [ 291 ]. In a mouse study, the cortical neurodegeneration caused by chronic exposure to this neurotropic parasite led to increased CX3CL1 expression accompanied by microglia activation [ 292 ].…”
Section: The Role Of Changes In Cx3cl1-cx3cr1 and Cd200-cd200r Interamentioning
confidence: 99%
“…Of the seven studies, three originated from Iran [ 11 , 26 , 29 ], three from Turkey [ 27 , 37 , 38 ], and one from Mexico [ 28 ]. Published between 2010 and 2017, all studies were based on case-controlled design.…”
Section: Resultsmentioning
confidence: 99%
“…Ramezani et al [ 26 ] suggested T. gondii infection contributed to an increased risk of PD, and Miman et al [ 27 ] also considered T. gondii might be involved in the development of PD. To the contrary, Alvarado-Esquivel et al [ 28 ] and Oskouei et al [ 29 ] indicated no association was observed between T. gondii infection and PD, Fallahi et al [ 11 ] found that T. gondii infection could not be a risk factor for PD. To date, and no meta-analysis was conducted to combine the available evidence.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, infection with T. gondii has been associated with reflexes impairment [ 25 ], epilepsy [ 26 , 27 ], Parkinson’s disease [ 28 ], and Alzheimer’s disease [ 29 ]. However, other studies found no association between T. gondii infection and Parkinson’s disease [ 30 , 31 ] and Alzheimer’s disease [ 32 ]. Remarkably, in a murine model, neuroinflammatory response following chronic toxoplasmosis reduced the accumulation of ß-amyloid plaques, ameliorating the hallmark of Alzheimer’s disease [ 45 ].…”
Section: Discussionmentioning
confidence: 99%